2011
DOI: 10.17221/217/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of temperature, pressure and low pH on the amplification of DNA of plant derived foods

Abstract: Bergerová E., Godálová Z., Siekel P. (2011): Combined effects of temperature, pressure and low pH on the amplification of DNA of plant derived foods. Czech J. Food Sci., 29: 337-345.The effect of food processing on the DNA integrity was studied by means of PCR amplification of soybean, transgenic MON 810 and non-transgenic maize, bean, and pea. The degree of DNA degradation was checked by PCR and visualised by agarose gel electrophoresis. The conditions of technological treatment such as temperature, pH, press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 22 publications
2
21
1
Order By: Relevance
“…Thermal treatment had a relatively more dramatic effect on the exogenous gene than the endogenous one (5) and our results are in agreement with that. The degree of DNA degradation in a specific food product can be predicted if the processing parameters are available (38).…”
Section: Quantitative Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal treatment had a relatively more dramatic effect on the exogenous gene than the endogenous one (5) and our results are in agreement with that. The degree of DNA degradation in a specific food product can be predicted if the processing parameters are available (38).…”
Section: Quantitative Pcrmentioning
confidence: 99%
“…The Japanese government requires mandatory labelling when GMO material is present in the top three raw ingredients and accounts for 5 % or more of the total mass (38), while the EU regulations require labelling of the foods that contain 0.9 % or more of GMO DNA or protein. Starting with labelled raw soybean, GMO content in the final product, tofu, was below the labelling threshold during processing.…”
Section: Quantitative Pcrmentioning
confidence: 99%
“…high temperature, pH, etc. ), DNA as a molecule highly resistant to various physical processes can be found in traces enabling testing for GM DNA presence (Bergerová et al 2011). Also, it has been found that food processing has no practical consequences for the quantification of transgenic content in foods (Bergerová et al 2010).…”
mentioning
confidence: 99%
“…The efficacy of PCR strongly depends on the DNA stability during food processing and on the efficiency of DNA recovery from food samples (Meyer et al 1996;Straub et al 1999;Gryson et al 2008;Bergerová et al 2010Bergerová et al , 2011. The quantification of food components can be nega-tively influenced by processing (Gryson et al 2008;Hrnčírová et al 2008;Bergerová et al 2010Bergerová et al , 2011.…”
mentioning
confidence: 99%
“…The quantification of food components can be nega-tively influenced by processing (Gryson et al 2008;Hrnčírová et al 2008;Bergerová et al 2010Bergerová et al , 2011.…”
mentioning
confidence: 99%